A methodological approach to couples therapy using a conjoint relational drawing process for the description of and intervention with relational patterns and meaning‐attributions. Issue 4 (24th August 2018) - Elisa Molina, María; Tapia‐Villanueva, Luis; Fossa, Pablo; Pereira, Ximena; Aspillaga, Carolina; de la Puerta, Sofía
Abstract : The consultants' observation and understanding of relational patterns in couples therapy is a main therapeutic objective and a resource for change. The Conjoint Relational Drawing Process (CRDP) methodology uses a drawing technique to enable the display and efficient observation of relational patterns. It was designed to address the relational process in couples therapy. Two couples participated in making a conjoint drawing that was video‐recorded and later observed and analysed by the couple and the therapist and the researchers. The relational pattern descriptions and meaning attributions about the video‐recorded drawings were analysed in the therapeutic and research contexts. As a result, new perspectives regarding relational patterns and meaning attributions emerged, revealing modes of interaction that allowed new viewpoints about difficulties and ways forward. This approach for the clinical application of CRDP contributed to the evaluation and intervention in the couples' therapy, and enabled issues to be defined early in the process. Abstract : La observación y comprensión, por parte de los terapeutas, de los patrones relacionales en la terapia de pareja es un objetivo terapéutico principal y un recurso para el cambio. La metodología del Proceso de Dibujo Relacional Conjunto (PDRC) usa una técnica de dibujo para permitir la visualización y observación eficiente de patrones relacionales. Dicha técnica fue diseñada para abordar el proceso relacional en la terapia de pareja. Dos parejas participaron en un hacer un dibujo conjuntamente y esta tarea fue grabada en video y posteriormente se observó y analizó por la pareja, el terapeuta y los investigadores. Las descripciones de los patrones relacionales y las atribuciones de significado sobre los dibujos grabados en video se analizaron en los contextos terapéuticos y de investigación. Como resultado surgieron nuevas perspectivas con respecto a los patrones relacionales y las atribuciones de significado, revelando modos de interacción que permitieron nuevos puntos de vista sobre las dificultades y las formas de avanzar. Este enfoque para la aplicación clínica del PDRC contribuyó a la evaluación y la intervención en la terapia de pareja, y permitió definir los problemas al principio del proceso. Abstract : 咨询师在夫妻治疗中对关系模式的观察和理解是主要的治疗目标和产生变化的源泉。联合关系绘图法（CRDP）使用绘画技术使关系模式得到呈现和有效观察。它旨在处理夫妻治疗中的关系过程。两对夫妇参与了联合绘图，过程被录像并且之后由这对夫妇以及治疗师和研究人员进行了观察和分析。在治疗和研究两种语境中分析了关于视频记录中的绘图的关系模式描述和意义归因。结果，涌现了关于关系模式和意义归因的新观点，揭示了产生关于目前困难和前进方向的新观点的互动模式。这种CRDP的临床应用方法有助于夫妻治疗中的评估和干预，并使问题能够在早期就得到确定。